Efektivitas Penerapan Media Big Book dan Penggunaan Gaya Belajar Siswa terhadap Penguasaan Kosa Kata Bahasa Arab Kelas IV di SD Islam Surya Buana Malang - St Nurhafsa Jalil (Matluba: Jurnal Pendidikan Bahasa dan Budaya Arab, 2024)
Abstract This study aims to determine (1) the effectiveness of the use of big book media on the mastery of Arabic vocabulary for Class IV at SDI Surya Buana Malang, (2) Students' learning styles towards mastery of Arabic vocabulary for Class IV at SDI Surya Buana Malang, and (3) comparison of the effectiveness between the use of the big book and student learning styles on the mastery of Arabic vocabulary for Class IV at SDI Surya Buana Malang. This research is a type of quantitative research and the research method used is descriptive method with normality test, linearity test, multicollinearity test, and hypothesis testing. Data collection techniques include measurement, and data measurement tools, namely questionnaires and documentation. The results of this study indicate that (1) Big book media is effectively used to master Arabic vocabulary with tcount 3,468 > ttable 2,001 with a significant value of 0.001 < 0.05, (2) Effective student learning styles are used to master language vocabulary. Arabic with the acquisition of tcount 3,464 > ttable 2,001 with a significant value of 0.001 < 0.05, and (3) Big book media and learning styles have a causal effect on Arabic vocabulary with the acquisition of tcount on the use of big book media 2.361 > ttable 2.001 with a value significant 0.022 < 0.05 and tcount on student learning styles 2.317 > ttable 2.001 with a significance value of 0.024 < 0.05. And the results of the F test analysis simultaneously (simultaneously) big book media and student learning styles have an effect on vocabulary mastery with a value of Fcount 9,244 > Ftable 3,13 with a significant value of 0.00 < 0.05.